A Short Retrospective Cytometric Note on Myeloblasts in Patients Suffering from Acute Myeloblastic Leukaemia, Myelodysplastic Syndrome and Chronic Myelocytic Leukaemia: Myeloblasts with a Narrow Cytoplasm without Azurophilic Granules Are Less Differentiated Committed Progenitor Stem Cells - Smetana, Karel; Klamová, Hana; Šimečková, Radka; Mikulenková, Dana (Folia biologica, 2024)
The maximal nuclear and cell body diameters of leukaemic agranular myeloblasts ("type 1" without azurophilic granules) were measured in bone marrow smears of patients suffering from acute myeloblastic leukaemia with minimal differentiation (M0 AML), without and with maturation (M1 and M2 AML), refractory anaemia with excess of myeloblasts (RAEB) and chronic phase of the myeloid leukaemia (CML) to provide more information on the cytoplasmic space estimate occupied by the nucleus. The largest size of the cytoplasmic space occupied by the nucleus in agranular myeloblasts was noted in M0 and M1 AML in comparison with M2 AML or RAEB, and especially with CML. Similarly, agranular myeloblasts with nuclear bodies occupying more than 90 per cent of the cell space were most frequent in M0 and M1 AML (> 50 %), less frequent in M2 and RAEB (~ 20 %) but very rare in CML (~ 5 %). According to electron microscopy, the very narrow cytoplasmic shell surrounding the nucleus in such myeloblasts did not possess any space for structural components characteristic of the granulocytic cell lineage. Thus, the basic morphology of these myeloblasts would correspond to morphological features of a less differentiated committed stem cell. It should be noted that such cells may be easily recognized in currently stained bone marrow or peripheral blood smears.
Keywords: myelodysplastické syndromy; senioři; Male; Leukemia, Myeloid, Acute; Female; Middle Aged; Aged; prekurzorové buňky granulocytů; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Myelodysplastic Syndromes; buněčná diferenciace; Cytoplasm; mužské pohlaví; ženské pohlaví; chronická myeloidní leukemie; Adult; Retrospective Studies; akutní myeloidní leukemie; Granulocyte Precursor Cells; retrospektivní studie; dospělí; lidé středního věku; Cell Differentiation; cytoplazma; lidé; Humans